Preparation of wastelage using poultry droppings with maize stover and its nutrient content as ruminant feed - Jamee, MDK; Kabir, AKMA; Islam, SMA; Hossain, MM; Khan, MRI (Bangladesh Journal of Animal Science, 2020)
An experiment was undertaken with caged layer excreta (CLE) treated maize stover and ensiled to investigate its potentiality as ruminant feed. Chopped maize stovers were preserved in plastic containers under airtight condition at room temperature based on the treatments as T0 (0% CLE), T1 (20% CLE), T2 (40% CLE) and T3 (60% CLE) to investigate physical quality, chemical composition, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) content at 0, 30, 60 and 90 days. The CP and Ash were increased (P<0.01) and DM, OM and CF were decreased (P<0.01) in all the treatments (T1, T2 and T3) compared to controlled T0. The OM content was decreased numerically with the ensiling time. The EE content was not significant (P>0.01) with the treatments and ensiling time. The OMD and ME content were increased (P<0.01) with the ensiling time from 0 to 90 days. The physical quality (color, smell, and hardness) of maize stover were improved by CLE added treatments (T1, T2 and T3) after ensiling but 60% CLE treatment had some pungent smell in 90 days and less OMD and ME value was observed than that of T2. Considering all the physical and chemical properties, among all the treatments, 40% and 60% CLE are acceptable for preparing wastelage. By comparing physical quality, nutritive value and chemical composition between 40% and 60% CLE treatments, the 60% CLE was better. Thus wastelage prepared from 40% CLE, 55% maize stover along with 5% molasses will be a potential source of ruminant feed as well as reduce the environment pollution by utilizing CLE. Bang. J. Anim. Sci. 2019. 48 (2): 75-84